Severn barrage proceedings of a symposium organized by the Institution of Civil Engineers, held in London on 8-9 October 1981. (Thomas Telford, 1982)
Discussing introduction and data collection, including model studies, and hydro-electric plant and transmission, these papers focus on caissons, embankments and ship locks, sediment movements and water quality, and conclude with further work and economics.